Strength, threat and cultural differences : a case study of Malaysian contractor in Indonesian construction project - Amer Faizal Aris, 1984-; Wan Zulkifli Wan Yusuf, supervisor; Fakulti Kejuruteraan Awam (2009)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2009